Nutra-Cosmeceuticals from Algae for Health and Wellness - Mourelle, María Lourdes; Domínguez, Herminia; Legido, Jose Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Microalgae and seaweeds are a renewable source of potent bioactive ingredients with confirmed positive impacts on health and wellness. The interest in-and awareness of-the need to improve quality of life and well-being has led to a greater consumption of nutraceuticals, as well as the use of cosmeceuticals for "well-aging". In this context, algae and microalgae are currently gaining immense popularity within the functional food, nutraceutical, and cosmeceutical industries. Recent advances in the characterization and evaluation of the biological properties of the whole material, fractions, or isolated compounds of algae and microalgae enable their use as ingredients for the development of novel nutraceutical and cosmeceutical products.